Quincke’s disease, a rare clinical disorder: a case report: - Gifari, Zikry (Faculty of Medicine, Universitas Trisakti, 2025)
BackgroundQuincke's disease, or isolated uvular angioedema, is a rare clinical condition and reports on its etiology and management remain limited. Most cases are linked to idiopathic conditions, food allergies, airborne allergens, medications (ACE inhibitors, NSAIDs), hereditary angioneurotic edema, oropharyngeal trauma, and infections. The disease may be encountered in any emergency setup and must be dealt with rapidly and with utmost vigilance to prevent progression and complications. Case descriptionA 24-year-old man visited the primary care clinic complaining of sudden throat discomfort upon waking. He described it as the sensation of a round object touching “the sides of his throat”. The sensation persisted despite swallowing. The patient denied having a sore throat, hoarseness, fever, or cough, and said that he had never experienced similar symptoms. The patient did not consume anything before he went to sleep and woke up with the sensation that something was 'stuck' in the back of his throat. Examination revealed an edematous and hyperemic uvula. Initial management ensured that there was no airway obstruction, with antihistamines and corticosteroids administered to relieve the uvular edema and discomfort. The patient said that the symptoms subsided within 72 hours and that there was no recurrence. ConclusionAwareness about this rare but acute condition, even in the background of unknown etiology, in all medical personnel is essential. Early diagnosis with appropriate management can prevent life-threatening airway obstruction and hypoxemia. Treatment depends on airway symptom severity. Thorough examination of each case is crucial, focusing on etiology and definitive management.